2019
DOI: 10.3892/mmr.2019.10438
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine protects aged rats from postoperative cognitive dysfunction by alleviating hippocampal inflammation

Abstract: The present study investigated the effect of dexmedetomidine on hippocampal inflammation and cognitive function in rats with postoperative cognitive dysfunction (Pocd). a total of 80 healthy male Sprague dawley rats were used, 72 of which developed Pocd. The rats were randomly divided into four groups: The control, model, low-dose and high-dose dexmedetomidine anesthesia groups. a Pocd model was established and dexmedetomidine was administered. cognitive function tests were performed and expression levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…In clinical patients, Dex application markedly reduced the expression of pro-in ammatory cytokines, such as IL-1β, TNF-α and IL-6 [43]. In rat model of POCD, Dex protected aged rats from cognitive dysfunction by decreasing hippocampal in ammation [44]. Here, although we did not detect the levels of in ammatory factors, the data showed that Dex signi cantly alleviated LPS induced neurite outgrowth and synaptic transmission damages.…”
Section: Discussionmentioning
confidence: 55%
“…In clinical patients, Dex application markedly reduced the expression of pro-in ammatory cytokines, such as IL-1β, TNF-α and IL-6 [43]. In rat model of POCD, Dex protected aged rats from cognitive dysfunction by decreasing hippocampal in ammation [44]. Here, although we did not detect the levels of in ammatory factors, the data showed that Dex signi cantly alleviated LPS induced neurite outgrowth and synaptic transmission damages.…”
Section: Discussionmentioning
confidence: 55%
“… 47 In a rat model of POCD, dexmedetomidine protects aged rats from cognitive dysfunction by decreasing hippocampal inflammation. 48 In our study, we did not measure levels of inflammatory factors, but nevertheless our data showed that dexmedetomidine significantly alleviated LPS-induced neurite outgrowth and defects in synaptic transmission. Also, currently in this paper, we only used primary cultured hippocampal neurons to observe the effect, and an animal model should be applied to further evaluate of the role of dexmedetomidine in POCD and the detailed mechanism should be investigated.…”
Section: Discussionmentioning
confidence: 68%
“…Dexmedetomidine can suppress hippocampal inflammation caused by surgical trauma and can effectively improve cognitive function after surgery in rats. (Chen et al 2019). In this study, dexmedetomidine inhibited sleep deprivation-induced production of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%